47‐1: Display Outdoor Visibility Enhancement Using Adaptive Tone Mapping. Issue 1 (28th June 2022) - Kim, Seungwan; Park, Deoksoo; Song, Byoungju; Lee, Sanghoon
Abstract : In this document, we propose an image tone mapping method enhancing the image visibility in outdoor environment. The proposed method improves the outdoor visibility of the displayed image in two aspects: brightness enhancement and content adaptive contrast enhancement. From the experiment results, it is confirmed that the proposed method improves the brightness and the contrast at the same time and enhances outdoor visibility effectively even with the limited dynamic range of the display device. Compared to conventional methods, proposed method has higher flexibility and effectiveness. This method is already utilized on the mobile devices for outdoor visibility enhancement and we expect to apply it to the automotive platforms.